Constraints to Rural Women's Participation in Extension Activities in Tikrit District, Salah al-Din Governorate (International Journal of Environmental Sciences, 2025)
The research aimed to identify the obstacles to rural women's participation in extension activities in Tikrit District, Salah al-Din Governorate, in general, and to determine the correlation between these obstacles and independent variables such as (age, education level, household size, household income, and type of agricultural activity). The study population included all rural women in Tikrit District who held agricultural contracts and worked in them, as recorded by the Tikrit Agricultural Directorate, totaling (451) women. After excluding the exploratory sample of (30) respondents from the total population, the study population became (421). A simple random sample was selected with a percentage of (27%) of the respondents, resulting in a total of (114) respondents who participated in the study. A questionnaire consisting of two sections was developed: the first section covered the independent variables of rural women, while the second section addressed three areas: (obstacles specific to rural women, obstacles related to agricultural extension, and social obstacles). It contained (42) statements, each representing an obstacle faced by rural women in participating in extension activities, distributed across the research areas as follows: (16, 13, and 13 statements, respectively).The result indicated that the level of obstacles encountered by rural women in the study area was high, leaning towards the average. Additionally, the results demonstrated a significant correlation between rural women's participation in extension activities and most of the factors examined. This underscores the numerous challenges they face across all studied domains and emphasizes the importance of these factors in influencing rural women's involvement in extension activities. The researchers recommend developing solutions to address the obstacles faced by rural women and focusing on the factors with a significant correlation to their participation. This can be achieved through awareness campaigns in rural communities to highlight the role of women in society.